Spatial analysis of mental health and suicide clustering among older adults in North Carolina: An exploratory analysis - Sophia C. Ryan; Jennifer D. Runkle; Lauren M. Andersen; Margaret M. Sugg (Elsevier, 2022)
Late-in-life suicide is a major public health issue, with adults over 65 comprising 18% of all suicide deaths. Yet, little research has identified geographic concentrations of older populations at-risk for the psychological conditions in the pathway of suicide. This research identified spatial clustering of suicide, anxiety, depression, and self-injury among older adults in North Carolina from 2009-18 and the individual and area-level factors influencing high-risk clusters. Kulldorff's spatial scan statistic identified significant spatial clusters of suicides, using data collected from the violent death reporting system, and anxiety, depression and self-injury, using emergency department admissions data for older adults aged 65 years and over. Logistic regression and generalized estimating equations were used to examine the influence of multiple contextual variables (e.g., rural-urban commuting area codes, racial segregation) and compositional variables (e.g., race, insurance) within high-risk cluster locations. High-risk suicide, anxiety, and depression clusters were identified in the western and northwestern regions of the state, whereas self-injury clusters were predominantly located in central and southeastern North Carolina. Low-income communities were associated with a higher risk of clustering for all mental health outcomes, and primarily Black communities were associated with an increased risk of self-injury clustering. Findings can be applied to public policy to focus suicide prevention efforts on older adults, particularly in low-income communities in rural Appalachia and the central, southeastern portion of North Carolina.